Limb ischemia-reperfusion and blood loss as factors in the development of pulmonary oxidative stress - Volotovska Наталія; Dobrorodniy Андрій (Psychosomatic Medicine and General Practice, 2025)
The lungs are among the organs most sensitive to systemic oxidative stress that develops during blood loss and ischemia–reperfusion syndrome (IRS). Excessive formation of reactive oxygen species (ROS), combined with depletion of antioxidant defenses under acute hypovolemia and trauma, leads to structural damage of lung tissue. However, the effects of combined injuries involving limb ischemia–reperfusion with blood loss or mechanical trauma on oxidative protein modification in the lungs remain poorly understood. This study investigated oxidative protein modification in lung tissue and quantitative changes in ROS-producing leukocytes in the blood of rats exposed to isolated IRS, blood loss, mechanical trauma, or their combinations. Two hundred sixty male white rats were divided into five experimental groups and a control group. Ischemia was induced by applying a rubber tourniquet for 2 hours, followed by reperfusion. Oxidative protein modification was assessed using 2,4-dinitrophenylhydrazine, and ROS-producing leukocytes were measured by flow cytometry. Isolated IRS caused an early increase in ROS-producing leukocytes, which intensified by day 3. Blood loss produced an even higher initial rise. The combined models demonstrated the most pronounced and prolonged oxidative imbalance, with a sustained elevation of ROS-producing leukocytes and maximal oxidative protein modification in lung tissue. These findings indicate that combined injuries involving IRS and blood loss or trauma significantly exacerbate oxidative lung damage, highlighting the importance of targeting oxidative stress in early post-traumatic organ protection. Key words: lungs; blood loss; ischemia-reperfusion syndrome; trauma; hemostatic tourniquet; protein oxidative modification; reactive oxygen species